Pengawasan dalam Manajemen Pendidikan Islam - Imam Muhayat (Widya Balina, 2018)
An improving of the education quality can be required at an educational supervision level. The word supervision as a form of supervision has a dual role that is academic, and clinical supervisions. The first is internal product and the second is more in the development of human resource competencies that carry out product realization. The word phrase appears the word supervisor, means observer. The role of the supervisor has to finds or identifies the capabilities and inability of the implementing personnel of the activity. The impact of these competencies affects the implementation of the program that has been determined. Therefore, in supervision activities, it is always necessary to report on the activities being carried out on the strengths and weaknesses of the implementation of these activities are immediately known well. The context of supervision in the millennial century with advances in technology and information requires policy makers and policy makers to understand the work space they carry out. The contents of the implementation of the activities to develop on increasingly information. Both, directly and indirectly, have influenced the results of the activities achieved. The context of supervision on the islamic education management which is at the level of norms and values ​​as an asset that cannot be valued only counts the completeness of the program, but also the indicators in the implementation of the program must be able to be controlled according to the predetermined program, so that future implications can be achieved, estimated clearly and thoroughly.